Regulation of the Optical Properties of Cellulose Nanocrystal Films by Sealed Deposition Treatment - Chenyu BAI; Yuxing ZHOU; Ranran CUI; Zhibiao CHEN; Xupeng LIANG; Tao MA; Yi SONG (Shipin gongye ke-ji, 2024)
Cellulose nanocrystal (CNC) can self-assemble and arrange at specific concentrations, imparting unique optical properties to the system. This paper investigated the effects of sealed deposition time and CNC concentration on the formation and alignment of cholesteric liquid crystals within the naturally dried films by analyzing the changes of CNC films in macroscopic color, UV-vis spectra, polarization optics, microscopic morphology, and crystal structure to elucidate the mechanism of CNC self-assembly behavior during the formation of CNC films. The results showed that when the sealed deposition time was extended to 48 h, the structural color development range and the long-range ordering of the cholesteric phase structure of CNC films were considerably enhanced. As the concentration increased, the CNC particle spacing decreased, the torsion angle between neighboring particles increased, and the pitch was compressed, decreasing from 480 nm to 344 nm. The results of polarized light microscopy analysis demonstrated that the sealed deposition treatment had a significant advantage in the formation of long-range ordered cholesteric phase structure in high-concentration CNC suspensions. The results of this research indicated that prolonging the sealed deposition time and increasing the CNC concentration could enhance the improvement of long-range orderliness in the films and promote the formation of cholesteric phase structural domains. This further improved the scientific basis for the preparation of CNC-based smart packaging materials and had a positive effect on the development of new visual food packaging and inspection materials.